The hBN Nanoparticles as an Effective Additive in Engine Oil to Enhance the Durability and Performance of a Small Diesel Engine - Abdollah, Mohd Fadzli bin; Abdullah, Muhammad Ilman Hakimi Chua; Amiruddin, Hilmi; tamaldin, noreffendy; Mat Nuri, Nur Rashid (2014)
With the increase in the number of vehicles, the problems with fuel consumption and environmental pollution are becoming more prominent. The use of an energy-conserving and emission-reducing automotive engine oil additive would have a great impact on energy conservation and environment protection. However, such an additive would need to enhance, or at least maintain the key lubrication properties. Thus, in this work, the potential of hexagonal boron nitride (hBN) nanoparticles as effective additive in SAE 15W40 diesel engine oil, to enhance the engine performance and simultaneously reduce frictional wear on the contact surfaces was studied.